Contemporary issues in business and economics in Vietnam and other Asian emerging markets - Chia-Lin Chang; Duc Hong Vo (Journal of Risk and Financial Management, 2020)
This Special Issue publishes high quality papers on contemporary issues in business and economics in Vietnam and other Asian emerging markets. These papers were accepted and presented at the 2019 Vietnam's Business and Economics Research Conference (VBER2019) organized by Ho Chi Minh City Open University, Vietnam in July 2019. Emerging issues in business and economics from Vietnam and other emerging markets in the Asian region have been addressed from various angles, from economics, finance, and statistics to management science. Five out of the 14 studies in this book were conducted to investigate various issues in relation to the Asian region such as the exchange rate regime in Asia, financial inclusion, and financial development and income inequality in Asian emerging markets. Seven studies were conducted in response to emerging business and economic issues in Vietnam such as fiscal decentralization, urbanization, foreign direct investment, and corporate financial distress. Other papers even considered various relevant aspects from the United States and Europe to the Asian region including double taxation treaties and agricultural shocks to the oil price. The findings from these papers are useful for practitioners, policymakers, and academics.
Keywords: 330; Vietnam; financial inclusion; fiscal decentralization; economic growth; financial development; exchange rate; Asian region